Coryfeus of lichen flora geographical analysis (to the 100th anniversary of the birth Mariya Florianivna Makarevich) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Coryfeus of lichen flora geographical analysis (to the 100th anniversary of the birth Mariya Florianivna Makarevich)